Data Protection Using Elliptic Curve Cryptography - Subhashini, M; Srivaramangai, P (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is a network-based service that provide sharing of resources such as virtual machine, storage, network, software and applications etc. It helps to reduce capital costs since that cloud users only need to rent resources according to their requirements and pay the services they use. It is very flexible since users can access its service in any place through intranet. However, a variety of security concerns such as integrity, availability and privacy act as barriers for cloud users to adopt the cloud service. Among all of these concerns, security of data is key concern holding back cloud adoption for individual or companies. The main purpose of this paper will introduce a method to protect data by using Elliptic Curve cryptography algorithm, how this algorithm works, and using ECC in data security of cloud computing.